Die hard: Probability of default and soft information - Giampaolo Gabbi; Michele Giammarino; Massimo Matthias (Risks, 2020)
The research aims to verify whether the credit risk of small and medium-sized enterprises can be estimated more accurately using qualitative variables together with financial information from reports. In our paper, we select qualitative variables within the conceptual framework of the balanced scorecard to assess the credit quality of Italian companies of various sizes, from micro to medium. Data were collected to estimate the company's resilience following the shock of the financial crisis of 2007-2008. The analysis based on customer size, processes, knowledge, and corporate finance, synthesized with balanced scorecard methodology, allows us to estimate the resilience of companies in a period of crisis. The research highlights the important contribution of qualitative variables for the estimation of credit risk. The implications concern both financial intermediaries and their supervisory functions, and regulators for rating models based on soft forward and countercyclical variables.
Keywords: 330; modeling credit risk; qualitative variables; rating; balanced scorecards; SME